Optimal channel allocation in heterogeneous wireless networks based on Stackelberg game. (8th June 2020) - Mahmoodzadeh, Azar; Agahi, Hamed
Optimal channel allocation in heterogeneous wireless networks enhances the coverage of mobile networks without need to provide new hardware equipment. In this paper a method based on the user cooperation by means of the game theory for optimal channel allocation in heterogeneous wireless networks, is presented. In the proposed approach, using the Stackelberg game, operators play the role of leaders while users are considered as followers. Then, the cooperation of the users for receiving different services according to their need in unlicensed spectrum is investigated. Improvement of some performance measures such as increase in channel gain and transmission power and decrease in interference to Wi-Fi users shows that this approach can enhance the efficiency of both operators and users with respect to the number of users and Wi-Fi access points. Comparing with other cooperation methods, the effectiveness of the proposed method in the efficiency of operators and users is demonstrated.